Can Heart Valve Decellularization Be Standardized? A Review of the Parameters Used for the Quality Control of Decellularization Processes - Naso, F.; Gandaglia, A. (Frontiers in Bioengineering and Biotechnology, 2022)
When a tissue or an organ is considered, the attention inevitably falls on the complex and delicate mechanisms regulating the correct interaction of billions of cells that populate it. However, the most critical component for the functionality of specific tissue or organ is not the cell, but the cell-secreted three-dimensional structure known as the extracellular matrix (ECM). Without the presence of an adequate ECM, there would be no optimal support and stimuli for the cellular component to replicate, communicate and interact properly, thus compromising cell dynamics and behaviour and contributing to the loss of tissue-specific cellular phenotype and functions. The limitations of the current bioprosthetic implantable medical devices have led researchers to explore tissue engineering constructs, predominantly using animal tissues as a potentially unlimited source of materials. The high homology of the protein sequences that compose the mammalian ECM, can be exploited to convert a soft animal tissue into a human autologous functional and long-lasting prosthesis ensuring the viability of the cells and maintaining the proper biomechanical function. Decellularization has been shown to be a highly promising technique to generate tissue-specific ECM-derived products for multiple applications, although it might comprise very complex processes that involve the simultaneous use of chemical, biochemical, physical and enzymatic protocols. Several different approaches have been reported in the literature for the treatment of bone, cartilage, adipose, dermal, neural and cardiovascular tissues, as well as skeletal muscle, tendons and gastrointestinal tract matrices. However, most of these reports refer to experimental data. This paper reviews the most common and latest decellularization approaches that have been adopted in cardiovascular tissue engineering. The efficacy of cells removal was specifically reviewed and discussed, together with the parameters that could be used as quality control markers for the evaluation of the effectiveness of decellularization and tissue biocompatibility. The purpose was to provide a panel of parameters that can be shared and taken into consideration by the scientific community to achieve more efficient, comparable, and reliable experimental research results and a faster technology transfer to the market.